DIGITAL TRANSFORMATION OF EDUCATION DURING AND POST COVID-19 ERA: THE SOCIAL IMPACT ON ADOLESCENTS - Dr Tajuddeen Sa’ad,; Mr. Ajibola F. O.,; Adewusi, O. Victoria, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The study was premised on investigating the impact of digital transformation on the education system in Nigeria especially during and post COVID-19 with adolescents being the focus. This study utilized a well- structured survey method, the questionnaires was prepared through Google Forms, and a total of 840 undergraduate students participated in this survey. All the data collected have been analyzed and presented in the form of tables. Statistical percentage was applied in the analysis of the data. From the findings therefore, it was confirmed that overuse of technology has negative social impact on young people. The findings revealed that although technology during COVID-19 has positive impacts on academic improvement on the students, it can also negatively affect their mental health. The study also found that the increasing dependency on technology can have detrimental effects on the nation's health.